The orientation of binding of human immunodeficiency virus reverse transcriptase on nucleic acid hybrids. - DeStefano, J J (1995)
The binding of HIV reverse transcriptase (RT) to heteroduplexes was examined using a substrate consisting of a 42 nt chimeric nucleic acid composed. (5'-->3') of 23 nt of RNA and 19 of DNA. This chimera was hybridized to an internal region of a relatively long complementary DNA or RNA. When the chimera was bound to DNA and conditions limiting cleavage to a single binding event between the enzyme and substrate were employed initial RNase H-directed cleavages occurred 19-21 nt from the chimera 5'-terminus. A 42 nt strand identical in sequence to the chimera and composed of only RNA was cleaved at the same locations. Reducing the length of the DNA portion of the chimera from 19 to 7 nt did not alter the cleavage positions, suggesting that cleavage was not coordinated by the DNA 3'-terminus. Under the same conditions cleavage was not detected when the chimera was bound to RNA. In contrast, addition of dNTPs to the DNA 3'-terminus of the chimera occurred only when the chimera was bound to RNA. The results support preferable binding of RT to RNA-DNA versus DNA-DNA hybrid regions and a model in which the orientation of binding to heteroduplexes is 5'-->3' (relative to the RNA strand), polymerase to RNase H active site, with sites associated with the DNA and RNA strand respectively.